Intercolonial Cooperation and the Building of St. Paul Island and Scatarie Island Lighthouses, 1826-1840 - Tingley, Zachary A.; Mancke, Elizabeth (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2022)
A dramatic increase in transatlantic commerce and immigration during the 1820s resulted in numerous shipwrecks in British North America, with the lack of coastal lighthouses in remote locations a particular problem. Negotiations began in 1826 between the Maritime colonies plus Lower Canada and the imperial government on ways to light remote coasts, and in 1835 the Colonial Office agreed to fund lighthouses on St. Paul and Scatarie islands on the route into the Gulf of St. Lawrence if the colonies funded their maintenance. The resulting three lighthouses and two humane stations redefined navigational safety as a shared responsibility of the imperial and colonial states worldwide.